BIO320: Introduction to Biological Diversity / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2021)
This course gives information about the diversity of life on earth from the simplest and primitive organisms to more complex and advanced organisms. It also covers how living things are categorized into groups based on their common features, unique life history and evolutionary relationship.